2016
DOI: 10.1002/2016wr018769
|View full text |Cite
|
Sign up to set email alerts
|

Push‐pull tracer tests: Their information content and use for characterizing non‐Fickian, mobile‐immobile behavior

Abstract: Path reversibility and radial symmetry are often assumed in push‐pull tracer test analysis. In reality, heterogeneous flow fields mean that both assumptions are idealizations. To understand their impact, we perform a parametric study which quantifies the scattering effects of ambient flow, local‐scale dispersion, and velocity field heterogeneity on push‐pull breakthrough curves and compares them to the effects of mobile‐immobile mass transfer (MIMT) processes including sorption and diffusion into secondary por… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
18
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 34 publications
3
18
2
Order By: Relevance
“…(The literature review in Hansen et al . [] contains an extensive discussion of these assumptions.) Background groundwater flow (drift) and heterogeneity cause nonradial, hysteretic flow patterns and violate the LIFO assumption, complicating test interpretation by generating heavy tails that may spuriously be attributed to other causes [ Lessoff and Konikow , ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…(The literature review in Hansen et al . [] contains an extensive discussion of these assumptions.) Background groundwater flow (drift) and heterogeneity cause nonradial, hysteretic flow patterns and violate the LIFO assumption, complicating test interpretation by generating heavy tails that may spuriously be attributed to other causes [ Lessoff and Konikow , ].…”
Section: Introductionmentioning
confidence: 99%
“…Johnsen and Whitson [] presented analysis quantifying the effect of solute path hysteresis caused by background drift on push‐pull breakthrough curves obtained from homogeneous velocity fields and Hansen et al . [] studied this phenomenon numerically in heterogeneous velocity fields.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among various types of tracer test, the single-well push-pull test is a method of easy performance and no more logistical complexity with a modest cost and has been applied to estimate physical parameters such as longitudinal dispersivity, groundwater velocity, and effective porosity of the tested aquifer [8][9][10][11][12]. The push-pull test consists of three phases.…”
Section: Introductionmentioning
confidence: 99%
“…Eddy (or recirculation zone) acts as immobile zone and occurs due to the irregularities of apertures in a rough-walled fracture (Cardenas et al, 2009;Raven et al, 1988). Mass exchange between mobile and immobile zones is assumed to be diffusive, which is based on the mobile-immobile conceptual models and their relevant analytical equations that have been suggested to explain non-Fickian process (Cherubini, Giasi, & Pastore, 2013;Gao, Zhan, Feng, Fu, & Huang, 2012;Hansen, Berkowitz, Vesselinov, O 0 Malley, & Karra, 2016;Qian et al, 2011;Raven et al, 1988). Cardenas et al (2009) showed that tailing, due to a large eddy, was more persistent with an increase of the Reynolds number (Re) up to about 10.…”
mentioning
confidence: 99%